Genetics in inclusion body myositis. Issue 6 (November 2017) - Rothwell, Simon; Lilleker, James B.; Lamb, Janine A.
Abstract : Purpose of review: To review the advances in our understanding of the genetics of inclusion body myositis (IBM) in the past year. Recent findings: One large genetic association study focusing on immune-related genes in IBM has refined the association within the human leukocyte antigen (HLA) region to HLA-DRB1 alleles, and identified certain amino acid positions in HLA-DRB1 that may explain this risk. A suggestive association with CCR5 may indicate genetic overlap with other autoimmune diseases. Sequencing studies of candidate genes involved in related neuromuscular or neurodegenerative diseases have identified rare variants in VCP and SQSTM1. Proteomic studies of rimmed vacuoles in IBM and subsequent genetic analyses of candidate genes identified rare missense variants in FYCO1 . Complex, large-scale mitochondrial deletions in cytochrome c oxidase-deficient muscle fibres expand our understanding of mitochondrial abnormalities in IBM. Summary: The pathogenesis of IBM is likely multifactorial, including inflammatory and degenerative changes, and mitochondrial abnormalities. There has been considerable progress in our understanding of the genetic architecture of IBM, using complementary genetic approaches to investigate these different pathways.